Penerapan Media Papan Rantai Makanan dan Analisis Respon Siswa Kelas IV di SDN Kaliwates 2 Jember - Nabila Nurfuaida Yahya; Muhammad Suwignyo Prayogo; Elmi Hildania (Lembaga Pengembangan Kinerja Dosen, 2025)
Science learning in elementary schools requires a concrete and contextual approach so that students can understand abstract concepts such as ecosystems. This study aims to determine the effectiveness of the Food Chain Board media in improving the understanding of 5th grade students of SDN Kaliwates 2 about the concept of ecosystems. This study uses a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the use of this learning media can increase student involvement during the learning process, help them construct food chains independently, and strengthen their understanding of the interactions between living things in the ecosystem. This media also creates a more enjoyable and interactive learning atmosphere. Thus, the Food Chain Board media is effective for use in science learning for ecosystem material.